Acute BDNF treatment upregulates GluR1-SAP97 and GluR2-GRIP1 interactions: implications for sustained AMPA receptor expression. - Hussam Jourdi (Public Library of Science (PLoS), 2013)
Brain-derived neurotrophic factor (BDNF) plays several prominent roles in synaptic plasticity and in learning and memory formation. Reduced BDNF levels and altered BDNF signaling have been reported in several brain diseases and behavioral disorders, which also exhibit reduced levels of AMPAr subunits. BDNF treatment acutely regulates AMPA receptor expression and function, including synaptic AMPAr subunit trafficking, and implicates several well defined signaling molecules that are required to elicit long term potentiation and depression (LTP and LTD, respectively). Long term encoding of synaptic events, as in long term memory formation, requires AMPAr stabilization and maintenance. However, factors regulating AMPAr stabilization in neuronal cell membranes and synaptic sites are not well characterized. In this study, we examine the effects of acute BDNF treatment on levels of AMPAr-associated scaffolding proteins and on AMPAr subunit-scaffolding protein interactions. We also examine the effects of BDNF-dependent enhanced interactions between AMPAr subunits with their specific scaffolding proteins on the accumulation of both types of proteins. Our results show that acute BDNF treatment upregulates the interactions between AMPAr subunits (GluR1 and GluR2) with their scaffold proteins SAP97 and GRIP1, respectively, leading to prolonged increased accumulation of both categories of proteins, albeit with distinct mechanisms for GluR1 and GluR2. Our findings reveal a new role for BDNF in the long term maintenance of AMPA receptor subunits and associated scaffolding proteins at synapses and further support the role of BDNF as a key regulator of synaptic consolidation. These results have potential implications for recent findings implicating BDNF and AMPAr subunits in various brain diseases and behavioral disorders.